2016
DOI: 10.1039/c5fd00185d
|View full text |Cite
|
Sign up to set email alerts
|

The characterisation of diesel exhaust particles – composition, size distribution and partitioning

Abstract: A number of major research questions remain concerning the sources and properties of road traffic generated particulate matter. A full understanding of the composition of primary vehicle exhaust aerosol and its contribution to secondary organic aerosol (SOA) formation still remains elusive, and many uncertainties exist relating to the semi-volatile component of the particles. Semi-Volatile Organic Compounds (SVOCs) are compounds which partition directly between the gas and aerosol phases under ambient conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 42 publications
(55 reference statements)
6
77
1
Order By: Relevance
“…The compound class-dependant removal efficiencies for the investigated DOC were 39 ± 12 % and 83 ± 3 % for the aliphatics (branched and straight-chain) and singlering aromatics, respectively. A typical DOC is expected to remove 50 to 70 % of the total HC emissions (Johnson, 2001;Alam et al, 2016). For the investigated compounds, the total DOC HC removal efficiency is at the lower limit of this expectation.…”
Section: Doc Removal Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The compound class-dependant removal efficiencies for the investigated DOC were 39 ± 12 % and 83 ± 3 % for the aliphatics (branched and straight-chain) and singlering aromatics, respectively. A typical DOC is expected to remove 50 to 70 % of the total HC emissions (Johnson, 2001;Alam et al, 2016). For the investigated compounds, the total DOC HC removal efficiency is at the lower limit of this expectation.…”
Section: Doc Removal Efficiencymentioning
confidence: 99%
“…The removal of nalkanes in the DOC have been found to decrease with increasing carbon chain length, a result of the greater number of adjacent sites in the DOC required to achieve absorption (Yao, 1980;Russell and Epling, 2011), supporting the results shown here. However, recently Alam et al (2016) investigated the HC removal efficiency of a similar specification DOC (i.e. mixed platinum and rhodium) for C 12 to C 33 nalkanes, among other species.…”
Section: Doc Removal Efficiencymentioning
confidence: 99%
“…20 Such particles are liable to shrink by evaporation as they advect into cleaner air within the urban environment and are largely absent from particle size distributions measured at surrounding rural sites. Measurements in Barcelona have provided evidence for the contribution of particles formed by regional nucleation processes 21,22 and there appear to be contributions both from advection of particles formed outside of the city as well as a separate population of particles which form within the Barcelona atmosphere.…”
Section: Consequences Of Urban Atmospheric Properties the Points Raismentioning
confidence: 99%
“…The DOC removed 46 ± 10 % of the ∑SpVOC emissions, with 83 ± 30 3 % for the single-ring aromatics and 39 ± 12 % for the aliphatics (branched and straight-chain). A typical DOC is expected to remove 50 to 70% of the total HC emissions (Johnson, 2001;Alam et al, 2016). For the investigated compounds, the total DOC removal efficiency is at the lower limit of this expectation.…”
Section: Doc Removal Efficiencymentioning
confidence: 99%
“…Furthermore, it was found that the exhaust gas composition varied depending primarily on combustion efficiency and DOC HC removal efficienc y, both 30 which are strongly dependent on working temperature (Korin et al, 1999;Roberts et al, 2014;Majewski and Khair, 2006;Russell and Epling, 2011). Diesel exhaust emissions contain thousands of compounds ranging from ~ C5 to C22, with contributions of up to C33 from lubricant oil (Alam et al, 2016;Gentner et al, 2017). Only a proportion of these emissions were speciated in this study.…”
mentioning
confidence: 99%